BUILDING AN EFFECTIVE SYSTEM OF MANAGEMENT ACCOUNTING AT THE ENTERPRISES OF RETAIL TRADE - O. Andreeva; O. Diakonova (Вестник университета, 2017)
Very often among the current problems of owners and the management of the organization there is a full misunderstanding of results of activity in comparison to the spent resources, impossibility or big difficulties at control of implementation of plans and decision-making for effective correction of a situation. The main scientific and practical result of article in definition of a technique of creation of effective system of management accounting. A methodological basis of a research were the provisions and conclusions created in scientific works of domestic authors. Application of recommendations will allow to increase effective management of the enterprise.